Pedagogical Innovation can make Primary Mathematics Adaptable - Pant, Poonam; Pant, Vyomesh (JOURNAL OF INDIAN EDUCATION, 2015)
Mathematics is considered to be the most difficult subject to study. General perception is that mathematics is not made for all, whereas, the reality is that basic mathematics is not difficult for anyone. In fact, mathematics is required in every aspect of our life and learning basic mathematics is one of the emergent requirements of the modern era. Fear from mathematics or say ‘math anxiety’ is a bigger problem for a teacher rather to tackle a student who is bad in mathematics. We have tried to examine the situation and provided certain steps which a teacher may adopt so as to overcome the problem. In our view, with some changes in the teaching techniques, with use of certain devices and systemic improvement the scenario can be changed. We highlight the problems being faced in teaching of mathematics, especially in teaching of primary mathematics, and provide solutions to overcome these problems. It must be an endeavour of every teacher to present mathematics in the plate of every child with proper garnishing of supporting devices so as to make it adaptable for all.